Alzheimer's Disease — Perspective from Political Science: Public Policy Issues. Issue 3 (September 2018) - Blank, Robert H.
The paper outlines the policy context and summarizes the numerous policy issues that AD raises from the more generic to the unique. It posits that strong public fears of AD and its future prevalence projections and costs, raise increasingly difficult policy dilemmas. After reviewing the costs in human lives and money and discussing the latest U.S. policy initiatives, the paper presents two policy areas as examples the demanding policy decisions we face. The first focuses on the basic regulatory function of protecting the public from those who would exploit these fears. The second centers on the well-debated issues of advance directives and euthanasia that surround AD. Although more dialogue, education and research funding are needed to best serve the interests of AD patients and families as well as society at large, this will be challenging because of the strong feelings and divisions AD engenders.